An international survey of obesity and underweight in youth and adults with intellectual disabilities. Issue 3 (3rd July 2019) - McConkey, Roy; Sadowsky, Molly; Shellard, Amy
ABSTRACT: Background: Increased levels of obesity have been reported for people with intellectual disability based on data mostly gathered in high income countries. Likewise few studies internationally have focussed on underweight in this population. Method: Data on obesity and underweight were analysed from nearly 86, 500 youth and adults with intellectual disabilities drawn from 178 countries attending Special Olympic events. Results: Binary logistic regressions identified higher levels of obesity for athletes in high income countries – especially in North America – and for females and for adults aged 40 years and over; and for youth aged 8 to 10 years. Rates of underweight were higher for younger adults in low income countries of Asia-Pacific, and highest for males aged 11-13 from lower-middle income countries of Africa. Conclusions: Contrasting intervention strategies are needed globally to enable people with intellectual disabilities to achieve healthy weight.